A collaborative preservice program in AT and AAC - Kennedy, Marianne; Shiller, Barbara (Perspectives on Issues in Higher Education, 2004)
Keywords: dept.cmd

Evidence-based practice among speech-language pathologists: attitudes, utilization, and barriers. - Zipoli, Richard P Jr; Kennedy, Marianne (American Journal of Speech-language Pathology, 2005)
A total of 240 speech-language pathologists responded to a questionnaire examining attitudes toward and use of research and evidence-based practice (EBP). Perceived barriers to EBP were also explored. Positive attitudes toward research and EBP were reported. Attitudes were predicted by exposure to research and EBP practice during graduate training and the clinical fellowship year (CFY). Clinical experience and opinions of colleagues were used to guide decision making more frequently than research studies or clinical practice guidelines. Only exposure to research and EBP during the CFY predicted use of evidence-based resources. Respondents reported a decline in exposure to research and EBP as they moved from graduate training into the CFY. A lack of time was perceived as a barrier to EBP.
Keywords: *Attitude of Health Personnel; *Data Collection/sn [Statistics & Numerical Data]; *Evidence-Based Medicine; *Health Knowledge, Attitudes, Practice; *Speech-Language Pathology/st [Standards]; Clinical fellowship; Evidence-based practice; Humans; Practice issues; Research; Speech-Language Pathology/sn [Statistics & Numerical Data]; Speech-language pathology; Surveys and Questionnaires; United States; dept.cmd